Climate protection through biochar in German agriculture: Potentials and costs - Isabel Teichmann (DIW Economic Bulletin, 2014)
In recent years, there has been much discussion about biochar - a carbonaceous product made of biomass - as a promising technique for mitigating climate change. In particular, this method has the potential to remove carbon dioxide from the atmosphere for the long term by incorporating biochar into the soil while enhancing soil fertility at the same time. A research project conducted by DIW Berlin calculated the greenhouse gas mitigation potential and possible costs of using biochar in German agriculture. According to this study, approximately one percent of the greenhouse gas reduction target for 2030 could be met using biochar, but largely at a cost of over 100 euros per tonne of CO2. Ultimately, however, biochar's potential for reducing greenhouse gas emissions is limited by the availability of biomass. The possible agricultural benefits of biochar in the form of enhanced soil fertility could improve the greenhouse gas reduction potential and costs. This may be of particular relevance in tropical and subtropical regions.
Keywords: Q15; Q24; Q54; 330; biochar; soil carbon sequestration; climate change; agriculture